Optimized recombinant production of the bacteriocin garvicin Q by Corynebacterium glutamicum - Desiderato, Christian K.; Müller, Carolin; Schretzmeier, Alexander; Hasenauer, Katharina M.; Gnannt, Bruno; Süpple, Bastian; Reiter, Alexander; Steier, Valentin; Oldiges, Marco; Eikmanns, Bernhard J.; Riedel, Christian U. (Frontiers in Microbiology, 2024)
Bacteriocins are antimicrobial peptides applied in food preservation and interesting candidates as alternatives to conventional antibiotics or as microbiome modulators. Recently, we established Corynebacterium glutamicum as a suitable production host for various bacteriocins including garvicin Q (GarQ). Here, we establish secretion of GarQ by C. glutamicum via the Sec translocon achieving GarQ titers of about 7 mg L -1 in initial fermentations. At neutral pH, the cationic peptide is efficiently adsorbed to the negatively charged envelope of producer bacteria limiting availability of the bacteriocin in culture supernatants. A combination of CaCl2 and Tween 80 efficiently reduces GarQ adsorption to C. glutamicum. Moreover, cultivation in minimal medium supplemented with CaCl2 and Tween 80 improves GarQ production by C. glutamicum to about 15 mg L -1 but Tween 80 resulted in reduced GarQ activity at later timepoints. Using a reporter strain and proteomic analyses, we identified HtrA, a protease associated with secretion stress, as another potential factor limiting GarQ production. Transferring production to HtrA-deficient C. glutamicum K9 improves GarQ titers to close to 40 mg L -1 . Applying conditions of low aeration prevented loss in activity at later timepoints and improved GarQ titers to about 100 mg L -1 . This is about 50-fold higher than previously shown with a C. glutamicum strain employing the native GarQ transporter GarCD for secretion and in the range of levels observed with the native producer Lactococcus petauri B1726. Additionally, we tested several synthetic variants of GarQ and were able to show that exchange of the methionine in position 5 to a phenylalanine (GarQ M5F ) results in markedly increased activity against Lactococcus lactis and Listeria monocytogenes. In summary, our findings shed light on several aspects of recombinant GarQ production that may also be of relevance for production with natural producers and other bacteriocins.